2019
DOI: 10.1002/jcb.28493
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA DLX6‐AS1 promotes liver cancer by increasing the expression of WEE1 via targeting miR‐424‐5p

Abstract: Long noncoding RNAs (lncRNAs) played an important role in tumorigenesis and development of hepatocellular carcinoma (HCC). In this study, we first demonstrated that lncRNA DLX6 antisense RNA 1 (DLX6‐AS1) was upregulated in cancer tissues and cells lines compared with normal adjacent and cell line. Knock‐down DLX6‐AS1 by transfection with small interfering RNA (siRNA) suppressed cell proliferation, migration, and invasion of HCC cells. Cell cycle analysis showed that cells transfected with siRNA were arrested i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…By analyzing the cancer genome atlas (TCGA) database, we identified a survival-related lncRNA, DLX6-AS1, which was upregulated in GC. The lncRNA DLX6-AS1 is a 1990 bp non-coding transcript located at chromosomal band 7q21.3 that has been reported to be overexpressed in lung adenocarcinoma [12], hepatocellular cancer [13,14], renal cell cancer [15], osteosarcoma [16], glioma [17] and pancreatic cancer [18]. Nevertheless, the carcinogenesis and regulatory mechanism of DLX6-AS1 in GC remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing the cancer genome atlas (TCGA) database, we identified a survival-related lncRNA, DLX6-AS1, which was upregulated in GC. The lncRNA DLX6-AS1 is a 1990 bp non-coding transcript located at chromosomal band 7q21.3 that has been reported to be overexpressed in lung adenocarcinoma [12], hepatocellular cancer [13,14], renal cell cancer [15], osteosarcoma [16], glioma [17] and pancreatic cancer [18]. Nevertheless, the carcinogenesis and regulatory mechanism of DLX6-AS1 in GC remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Piao L et al reported that miR-424-5p expression is reduced in HCC patients and induces apoptosis of HCC cells by targeting and inhibiting YAP1 expression [28]. Li D et al observed that WEE1 is a target of miR-424-5p, and overexpression of WEE1 promotes the proliferation, migration and invasion of HCC cells [29]. Du H et al believed that miR-424-5p acting as a tumor suppressor gene can inhibit the invasive ability of HCC cells by directly regulating TRIM29, showing its potential to be a novel prognostic indicator [30].…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNA (lncRNA), defined as a group of transcripts with a length > 200 nucleotides with limited protein coding potential, have been implicated in the onset and development of different human cancers by chromatin remodeling, as well as transcriptional and post-transcriptional regulation [10,11]. For example, lncRNA DLX6-AS1 promotes liver cancer by increasing the expression of WEE1 via targeting miR-424-5p [12]; lncRNA MORT overexpression inhibits cancer cell proliferation in oral squamous cell carcinoma by downregulating ROCK1 [13]; lncRNAGIHCG induces cancer progression and chemoresistance and indicates poor prognosis in colorectal cancer [14].It has been found that lncRNA maternally expressed gene 3 (MEG3) with tumor suppressor activity was frequently either lost, mutated or decreased level in many human tumors and tumor derived cell lines [15]. For instance, lncRNA MEG3 inhibits the progression of prostate cancer by modulating miR-9-5p/QKI-5 axis [16]; Down regulation of lncRNA MEG3 promotes colorectal adenocarcinoma cell proliferation and inhibits the apoptosis by up-regulating TGF-β1 and its downstream sphingosine kinase 1 (SPHK1) [17]; lncRNA MEG3 suppresses the tumorigenesis of hemangioma by sponging miR-494 and regulating PTEN/PI3K/ AKT pathway [18].…”
mentioning
confidence: 99%